Legal Analysis Of Rights Related To Copyright (Neighbouring Rights) On Moral Rights And Economic Rights In Rebroadcasting The 2022 World Cup Aired By Television Stations In Indonesia - Pulungan, Atikah Sarah; Maria Kaban; Aflah (Talenta Publisher, Universitas Sumatera Utara, 2024)
Neighbouring Rights are exclusive right within copyrigtht law, pertaining to Performers Phonogram Producers, and Broadcasting Institutions. Broadcasting Institutions, as organizers of broadcasts, require broadcasting rights – permits mandatory for broadcasters. Indonesian television stations, in their broadcasting activities, possess both Moral Rights and Economic Rights. Moral Rights are inalienable rights inherent to the creator, while Economic Rights concern the economic exploitation of the creation. This research employs a normative library research methodology, focusing on collecting secondary data from primary, and tertiary legal sources. The regulation of international television broadcasting in Indonesia is governed by licensing procedures and legal provisions. Regarding Moral and Economic Rights in Indonesian television broadcasting, these encompass the right to broadcast, authorize others, or prohibit rebroadcasting, broadcast communication, fixation, and reproduction of broadcast fixations. These rights are intrinsically linked to the creator. The Legal Analysis of Related Rights (Neighbouring Rights) concerning Moral and Economic Rights of the 2022 World Cup rebroadcasts by Indonesian television stations involves obtaining prior authorization from the Indonesian Broadcasting Commission before commencing broadcasting activities. Monitoring and supervision of World Cup broadcasts in Indonesia are conducted by the Directorate General of Intellectual Property under the Ministry of Law and Human Rights.